Accuracy of Sonography in Plantar Plate Tears in Cadavers. (11th April 2017) - Stone, Michael; Eyler, William; Rhodenizer, Joshua; van Holsbeeck, Marnix
Abstract : Objectives: Sonography is often used in the evaluation of forefoot disorders, and its use has been suggested in the diagnosis of plantar plate tears. This study aimed to assess the accuracy of sonography in the diagnosis of plantar plate tears of the lesser digits using gross dissection as the reference standard. Methods: The second through fifth digits of 6 cadavers were examined with sonography to evaluate for plantar plate tears. The examination was performed by a single musculoskeletal radiologist in longitudinal and short axes, and plates were graded as torn or intact. The digits were then dissected by a single podiatrist blinded to the prior sonographic results to assess the integrity of the plates. Results: Ten plantar plates were graded as torn by sonography, all occurring in the distal plate near the phalangeal insertion. Seven of these plates were identified as torn on direct inspection. Fourteen plantar plates were found to be intact on sonography, 12 of which were intact on gross inspection. Overall, the accuracy, sensitivity, and specificity of sonography were 79.2%, 77.8%, and 80.0%, respectively. No correlation was seen between the accuracy of sonography and plate size, using plate number as a surrogate marker for plate size ( P = .822). Conclusions: Sonography is an appropriate modality in the setting of suspected plantar plate tears, with acceptable accuracy, sensitivity, and specificity. No decline in accuracy was seen with smaller plates. Thus, sonography may be especially useful when small anatomy or technical factors make magnetic resonance imaging challenging to perform and interpret.